Digital Marketing Trends in Management Research Topics in the Corporate Buying and Selling Market Sector: A Bibliometric Analysis - Kusuma, Vicky Ayu; Wijaya, Tony (JURNAL MANAJEMEN UNIVERSITAS BUNG HATTA, 2026)
The development of digital technology has changed marketing trends in marketing management literature. This study aims to analyse trends and directions in digital marketing research, identify dominant themes, and map the contributions of influential authors, journals, and countries, particularly in the context of corporate buying and selling market with digital marketing. The main problem is the lack of a systematic review that describes the conceptual dynamics and interconnections between researchers in this field. The method used is qualitative with a bibliometric analysis approach, using data from Scopus and VOSviewer software to visualise networks of keywords, authors, and research themes. From 280 documents published between 2020 and 2025, a significant increase in publications was found, peaking in 2024. The analysis identified six main clusters: brand promotion and image, consumer behaviour and purchase intent, buyer and salesperson perspectives, smart tourism and profit orientation, consumer credibility and trust, and e-marketing and digital innovation. The findings indicate a paradigm shift in digital marketing from one-way communication to interactive systems based on artificial intelligence and personalised consumer experiences. Research recommendations are directed towards exploring clusters that are still limited and strengthening data-based approaches for the effectiveness of digital marketing strategies in the corporate sector.